Analysis of the Influence of the Role of Influencers on Increasing Income in Liberica - Utari, Marti; Sari, Diah Novita; Rahmi, Lailatur; Devani, Ferizka Tiara; Mardiana, Mardiana (Journal of Research in Social Science and Humanities, 2024)
The role of influencers is a successful marketing strategy because in the digital era, users choose interesting content from influencers and people they follow over advertising and frequent use of social media. This research aims to determine "The Influence of the Role of Influencers on Increasing Income in Liberica". This research will use quantitative research methods, with a research sample of 56 respondents. "The research results show that multiple linear regression has a constant value with a positive sign of 17.882. The F test states that the role of influencers in increasing income in Liberica is 0.013 0.05. The T test states that the role of influencers (X1) produces a significance value of 0.00 0.05 and the calculated t value is 6.043 t table 1.673, and the R value is 0.119 or 11.2%.